A dictionary of weights, measures, and units - Fenna, Donald, 1932- (Oxford paperback reference., 2002)
Searchable database with over 1,500 entries providing clear definitions of all the units, prefixes, and styling of the Système International (SI), as well as industry-specific and traditional terms currently in use.